Measuring Healthcare Service Quality for Inpatients in Significant Hospital at Developing Country - Chu, Si Dung; Nguyen, Thuy Tran; Khong, Tan Sin (International Journal of Innovative Research in Medical Science, 2018)
Objective: Measuring inpatient healthcare service quality for inpatients of significant private general hospital in developing countries by the functional quality and Technical quality. Subject and method: Cross-Sectional study, measure consumers’ perceptions of inpatient in healthcare service quality for Private hospital by both in functional and technical quality, using the SERVQUAL instrument with five generic dimensions (the original 22 scores) for functional quality to combinate with the 8 dimensions (8 scores) for technical quality, study a significatn private hospital’s Triduc general hospital in Vietnam country; Most inpatients whole length of stay in General clinic department at the hospital, during from November 2013 to January 2014. Result: Altogether 230 persons were interviewed and 216 patients were identified by stratified random sampling. The functional quality by SERQUAL intrument had 5 items (22 scores) are the “Reliability”, “Responsiveness”, “Assurance”, “Empathy”,“Tangible” including and Technical quality by 8 item (8 scores); These items have highly patient satisfaction (PS) mean are “from 3.828 to 4.425”, and Cronbach alpha for the first construct of private are 0.882, 0.871, 0.845, 0.794, 0.864, 0.958, respectively; Responsiveness dimension with 4 items of the case is moved. After performing factor analysis, we have four final factors distinguish drawn are factor 1 (Reliability) with 15 variables, factor 2 (Assurance) with 4 variables, factor 3 (Tangible) with 3 variables, factor 4 (Technical quality) with 8 variables; the model had highly Corrected Item-Total Correlation of PS and reliability coefficient; 02 factors not achieve that distinction is worth understanding and guarantee. Conclusion: Adjusted research model for the private hospital have four contruct from levels of customer satisfaction about service quality is influenced by the SERVQUAL (3 items are responsivenes, reliability and tangibles with 22 scores) and Technical Quality intrument (8 scores). The model provides feedback on the quality of a private hospital experience from the adult inpatient’s perspective at the developing country.